Integrative structural and functional analysis of human malic enzyme 3: A potential therapeutic target for pancreatic cancer. Issue 12 (December 2022) - Grell, Tsehai A.J.; Mason, Mark; Thompson, Aaron A.; Gómez-Tamayo, Jose Carlos; Riley, Daniel; Wagner, Michelle V.; Steele, Ruth; Ortiz-Meoz, Rodrigo F.; Wadia, Jay; Shaffer, Paul L.; Tresadern, Gary; Sharma, Sujata; et al.
Abstract: Malic enzymes (ME1, ME2, and ME3) are involved in cellular energy regulation, redox homeostasis, and biosynthetic processes, through the production of pyruvate and reducing agent NAD(P)H. Recent studies have implicated the third and least well-characterized isoform, mitochondrial NADP + -dependent malic enzyme 3 (ME3), as a therapeutic target for pancreatic cancers. Here, we utilized an integrated structure approach to determine the structures of ME3 in various ligand-binding states at near-atomic resolutions. ME3 is captured in the open form existing as a stable tetramer and its dynamic Domain C is critical for activity. Catalytic assay results reveal that ME3 is a non-allosteric enzyme and does not require modulators for activity while structural analysis suggests that the inner stability of ME3 Domain A relative to ME2 disables allostery in ME3. With structural information available for all three malic enzymes, the foundation has been laid to understand the structural and biochemical differences of these enzymes and could aid in the development of specific malic enzyme small molecule drugs. Abstract : Malic enzymes; X-ray crystallography; Single particle Cryo-EM; Allostery; Drug discovery.